SIMILARITIES AND DIFFERENCES OF VOICE IN ENGLISH AND UZBEK LANGUAGE GRAMMAR - MURODOVA SIVINCH (TADQIQOTLAR.UZ, 2024)
This comparative study examines the concept of voice in the grammatical structures of English and Uzbek languages. Voice, which pertains to the relationship between the action or state expressed by the verb and its participants, reveals both convergences and divergences across these two languages. In English, the primary distinction is between active and passive voices, with the latter constructed using auxiliary verbs and past participles. Uzbek, a Turkic language, also features active and passive voices but employs distinct morphological markers and syntactic arrangements to convey them. The study highlights the syntactic, morphological, and functional similarities and differences, providing insights into how each language handles the agent-patient dynamic within sentences. The comparison underscores the influence of typological characteristics and historical developments on the grammatical expression of voice in both languages.